2009
DOI: 10.4049/jimmunol.0801324
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Adenosine A2B Receptors to Inflammatory Parameters of Experimental Colitis

Abstract: Inflammatory diseases influence tissue metabolism, significantly altering the profile of extracellular adenine nucleotides. A number of studies have suggested that adenosine (Ado) may function as an endogenously generated anti-inflammatory molecule. Given the central role of intestinal epithelial cells to the development of colitis, we hypothesized that specific Ado receptors would contribute to disease resolution in mucosal inflammation as modeled by dextran sodium sulfate (DSS) colitis. Initial profiling stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
165
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(179 citation statements)
references
References 52 publications
11
165
2
1
Order By: Relevance
“…As first step, we induced diabetic nephropathy in previously described Adora2b 2/2 mice. 23,[28][29][30][31][48][49][50][51] Similar to the preceding studies in Cd73 2/2 mice, we observed a more severe degree of diabetic nephropathy in Adora2b 2/2 mice without differences regarding systolic BP and blood glucose levels (Supplemental Figure 4, A and B), but a more severe degree of body weight loss ( Figure 5A), increased kidney weight (Figure 5B), and elevated urine (Figure 5C) and drinking ( Figure 5D) volumes. Determination of the GFR showed a more severe hyperfiltration in Adora2b 2/2 mice compared with diabetic control mice ( Figure 5E).…”
Section: Diabetic Nephropathy Is More Severe In Adora2bsupporting
confidence: 74%
“…As first step, we induced diabetic nephropathy in previously described Adora2b 2/2 mice. 23,[28][29][30][31][48][49][50][51] Similar to the preceding studies in Cd73 2/2 mice, we observed a more severe degree of diabetic nephropathy in Adora2b 2/2 mice without differences regarding systolic BP and blood glucose levels (Supplemental Figure 4, A and B), but a more severe degree of body weight loss ( Figure 5A), increased kidney weight (Figure 5B), and elevated urine (Figure 5C) and drinking ( Figure 5D) volumes. Determination of the GFR showed a more severe hyperfiltration in Adora2b 2/2 mice compared with diabetic control mice ( Figure 5E).…”
Section: Diabetic Nephropathy Is More Severe In Adora2bsupporting
confidence: 74%
“…Interestingly, other investigators have demonstrated more of an anti-inflammatory and protective role for A 2B AR receptors in ischemia-reperfusion injury (16,17) and murine colitis (13). Differences in experimental protocols, animal strains, and environmental conditions have been proposed as possible reasons for the discrepancies in the findings (13).…”
Section: Resultsmentioning
confidence: 99%
“…In the study, we found that upregulation of A 2B ARs occurs in TcdA-or TcdB-challenged human intestinal epithelial cells. Others have shown that both A 2A AR and A 2B AR are expressed during dextran sodium sulfate (DSS)-induced colitis (13), while A 2B AR is selectively induced in ischemia-reperfusion injury in mice (17). A 2A AR mRNA is not as prominently expressed as A 2B AR in epithelial cells; A 2A AR may be more localized in immune rather than epithelial cells in the intestinal tract (12,18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adora2b signaling, we next performed studies to identify the role of Adora2b expressed on different cell types. As previous studies had implicated Adora2b signaling on endothelia (32) or epithelia (33) in organ inflammation, we used a transgenic mouse line with a floxed Adora2b gene (34) . Indeed, mice with genetic deletion of the Adora2b in tubular epithelia retained dipyridamole-mediated kidney protection from ischemia, indicating that ENT inhibition-mediated kidney protection is independent of Adora2b expression on tubular epithelia ( Figure 9, A-E).…”
Section: Figurementioning
confidence: 99%